Eruption of First Permanent Molar Among a Group of Iraqi Children in Relation to Nutritional Status - Khalaf, Muna Saleem; Abdul-Wadood, Meena Osama; Khammas , Asmaa Mohammed (Scripta Medica, 2024)
Background/Aim: The timing of a tooth’s eruption can be affected by a variety of factors. The nutritional status has an impact on the development of a child’s body. The purpose of the study was to count the number of children aged 6 to 9 in an Iraqi Arab population who had erupted permanent first molars and to examine how nutritional status affected the timing and level of emergence. Methods: A total of 330 boys and girls, in first grade elementary school, made up the sample. First molars that had erupted were noted, along with the level of the eruption. Each child’s nutritional status was evaluated by recording their height and weight and body mass index (BMI) value was compared to the 2007 WHO reference. Results: Girls had higher number of erupted molars than boys did and a correlation between the number of erupted teeth and nutritional condition existed, with a higher mean number of erupted molars in obese children. Conclusion: BMI had an impact on the timing of the eruption of permanent first molars, a result that was primarily observed in females.